Effect of Diaphragmatic Breathing Exercise Leaflet on Reducing Blood Pressure of Hypertensive Elderly: An Integrated Health Care Delivery System - Nurwahidah,; Nurwahidah,; Fathoni, Akhmad; Syaiful, (International Journal of Psychosocial Rehabilitation, 2020)
Hypertension or high blood pressure is a vascular problem which causes the supply of oxygen and nutrients carried by blood being blocked to the tissues. The results of the Baseline Health Research (Riskesdas) reported in 2014 showed an increase in the national prevalence of hypertension in people aged over 18 years by about 37.1%. From 2007 to 2015. This study uses a quasy-experimental method, using a comparative pre-test and post-test, on 64 aged people. The research subjects were observed by measuring the blood pressure before and after activity. Data analysis used paired T-test with an α = 0.05. Significance based on ρ value